A nanocarbon fiber reinforced low-carbon magnesium-carbon refractory material and preparation method thereof

By introducing nanocarbon fibers into magnesium carbon refractory materials, combining raw materials such as electromelted magnesium sand and polymagnesium carboxylate, low-carbon magnesium carbon refractory materials with uniform distribution in nanocarbon fibers, the problem of degradation in performance during low carbonization is solved and the realization of the achievement of It has excellent oxidation resistance, thermal shock resistance and slag corrosion resistance.

CN116573922BActive Publication Date: 2025-02-11武汉钢铁有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310336181.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-02-11
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

During the low carbonization process of existing magnesium-carbon refractory materials, their oxidation resistance, thermal shock stability and slag corrosion resistance have significantly decreased, making it difficult to meet the smelting requirements of low carbon steel and clean steel.

Method used

Using nano-carbon fiber reinforced low-carbon magnesium carbon refractory materials, by adding electromelting magnesium sand, waste magnesium carbon bricks, polymagnesium carboxylate, magnesium citrate, mesophase asphalt, catalysts (such as nano-nickel or nano-iron) to the raw materials and Binding agents (such as thermosetting phenolic resins) are prepared by premixing, ball milling, pressurized molding and sintering processes to prepare low-carbon magnesium carbon refractory materials with uniform distribution of nanocarbon fibers.

Benefits of technology

The low-carbon content, excellent oxidation resistance, thermal shock stability and slag corrosion resistance of low-carbon magnesium carbon refractory materials are achieved, extending the service life of the material and reducing the consumption of graphite resources.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material, wherein the raw materials and their mass percentages include: 88% to 95% of fused magnesia sand, 0% to 3% of magnesium-carbon bricks, 0.5% to 4% of polycarboxylic acid magnesium, 0% to 0.5% of magnesium citrate, 0.3% to 3% of mesophase pitch, 0.05% to 0.6% of catalyst, and 0.1% to 2% of binder. The nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material obtained by the invention has low carbon content, uniform nano-carbon fiber distribution, excellent oxidation resistance, thermal shock resistance stability and slag erosion resistance; and the preparation method provided by the invention is simple and efficient, and is suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material and a preparation method thereof, belonging to the field of refractory materials. Background Art

[0002] The low carbonization of magnesium carbon (MgO-C) refractory is beneficial to reduce the carbonization effect of refractory on molten steel, reduce the use of non-renewable resources, and meet the purpose of green metallurgy. Because magnesium carbon refractory has excellent slag erosion resistance, thermal shock stability and oxidation resistance, and the preparation process is simple, it is widely used as lining material for electric furnaces, converters and refining furnaces. However, there are the following problems in the preparation and application of traditional magnesium carbon refractory: (1) a large amount of graphite resources are consumed; (2) high thermal conductivity leads to increased heat loss, which is difficult to meet the requirements of secondary refining process; (3) high carbon content easily causes carbonization of molten steel and pollutes molten steel, which is not conducive to the smelting of pure steel and ultra-low carbon steel. Therefore, the low carbonization of magnesium carbon refractory is in line with the purpose of green metallurgy, but with the decrease of carbon content, the oxidation resistance, thermal shock stability and slag permeability of magnesium carbon refractory also decrease significantly. In the application of electric furnaces, converters and refining furnaces, the specific manifestation is that the spalling resistance of magnesium carbon refractory is reduced and carbon is more easily oxidized. In view of the above problems, it is very important to study a new type of low-carbon magnesium-carbon refractory material, which can not only effectively reduce the carbon content, but also ensure that the material has good slag erosion resistance, thermal shock stability and oxidation resistance.

[0003] Chinese patent CN202210135113.7 discloses a low-carbon magnesium-carbon brick with excellent antioxidant properties, characterized in that, calculated by mass, the raw materials for its preparation include the following components: 50-100 parts of fused magnesia, 0.5-10 parts of metal aluminum powder, 1-10 parts of phenolic resin, 0.5-10 parts of B4C-TiN composite material, 0.5-10 parts of high-temperature asphalt, and 0.5-10 parts of graphite; in the B4C-TiN composite material, the volume fraction of B4C is 18%-33%, and the volume fraction of TiN is 67%-82%. Although this invention effectively improves the material's antioxidant and anti-molten steel scouring properties, it contains multiple elements such as Al, Ti, and N, which is not conducive to the production of clean steel. Chinese patent CN202111023818.1 discloses a low-carbon magnesium carbon brick with antioxidant properties, characterized by: according to weight, including 88-96 parts of fused magnesia, 1-3 parts of metal aluminum powder, 3 parts of resin, 1-3 parts of ZrB2-Cr7C3 composite material, 1-3 parts of high-temperature asphalt and 1-3 parts of -196 graphite; the volume fraction of ZrB2 in the ZrB2-Cr7C3 composite material is 15%-35%, and the volume fraction of Cr7C3 is 65%-85%. This invention effectively improves the antioxidant properties of the material, but contains Cr, which is very polluting to the environment, carcinogenic, and is not conducive to the development requirements of the green and environmentally friendly industry. Chinese patent CN201810613284.X relates to a nano-carbon enhanced low-carbon magnesium carbon brick and a preparation method thereof, wherein the nano-carbon content is 2%-4%, which is 50% of the carbon content of the current mainstream magnesium carbon brick. By adding nano-carbon, although the total carbon content is reduced by half, the raw material cost is saved and the service life of the magnesium carbon brick is extended; however, the nano-carbon added in the invention is difficult to be evenly dispersed in the raw materials, resulting in unstable slag corrosion resistance and strength properties of the low-carbon magnesium carbon brick, affecting the use effect of the material.

[0004] Therefore, in response to the above problems, it is very important to develop a low-carbon magnesium-carbon refractory material with low carbon content, uniform distribution of nanocarbon fibers, excellent oxidation resistance, thermal shock stability and slag erosion resistance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a low-carbon magnesium-carbon refractory material reinforced with nano-carbon fibers for electric furnaces, converters and refining furnaces in response to the deficiencies in the above-mentioned prior art. The present invention overcomes the problems of high carbon content, less than ideal slag erosion resistance, thermal shock stability and oxidation resistance of the existing magnesium-carbon refractory materials, and can meet the requirements of refractory materials for low-carbon steel, clean steel, etc.

[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0007] A nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material, the raw materials of which include fused magnesia sand, waste magnesium-carbon bricks, magnesium polycarboxylate, magnesium citrate, mesophase asphalt, a catalyst and a binder, wherein the catalyst is nano-nickel and / or nano-iron, and the binder is a thermosetting phenolic resin; the raw materials are as follows by mass percentage: 88% to 95% of fused magnesia sand, 0 to 3% of magnesium-carbon bricks, 0.5% to 4% of magnesium polycarboxylate, 0 to 0.5% of magnesium citrate, 0.3% to 3% of mesophase asphalt, 0.05% to 0.6% of catalyst, and 0.1% to 2% of binder.

[0008] According to the above scheme, the volume density of the low-carbon magnesium-carbon refractory material is 2.95-3.32 g / cm 3 , carbon content is 3.8% ~ 9.0%, compressive strength is 9.2 ~ 13.0MPa, refractoriness> 1760℃, thermal shock stability> 50 times, slag erosion resistance S c / S0<0.03.

[0009] According to the above scheme, the MgO content in the fused magnesia is greater than 97wt%; the particle size of the fused magnesia does not exceed 6mm, and the mass percentage of the particle size in the range of 0.088-1mm is 22%-30%, the mass percentage of the particle size in the range of 1-3mm is 29%-34%, and the mass percentage of the particle size in the range of 3-6mm is 32%-41%.

[0010] According to the above scheme, the magnesia carbon bricks are prepared by sorting the waste magnesia carbon bricks, removing the oxidized parts and residual impurities, crushing and ball milling them, and then screening them. The mass percentage of particles in the range of 0.088 to 1 mm is 50% to 80%, and the mass percentage of particles in the range of 1 to 3 mm is 20% to 45%; wherein the MgO in the treated magnesia carbon bricks is not less than 84.0wt%.

[0011] According to the above scheme, the polycarboxylate magnesium is one or both of polyacrylate magnesium or polymethacrylate magnesium, and the relative molecular weight thereof is greater than 10,000.

[0012] According to the above scheme, the nano nickel or nano iron is a powder with a particle size ranging from 10 to 40 nm; the nickel content of the nano nickel is greater than 98wt%, and the iron content of the nano iron is greater than 98wt%.

[0013] According to the above scheme, the mesophase asphalt is a coal-based mesophase asphalt with a relative molecular weight of 1000 to 6000 and a softening point of 400 to 500°C.

[0014] According to the above scheme, the specific gravity of the thermosetting phenolic resin is 1.20-1.25, and the solid mass percentage is 70%-85%.

[0015] The present invention provides a method for preparing a nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material, comprising the following steps:

[0016] (1) preparing raw materials according to the mass percentage of each raw material: 88% to 95% of fused magnesia sand, 0% to 3% of magnesia carbon brick, 0.5% to 4% of polycarboxylate magnesium, 0% to 0.5% of magnesium citrate, 0.3% to 3% of mesophase pitch, 0.05% to 0.6% of catalyst, and 0.1% to 2% of binder;

[0017] (2) premixing the fused magnesia, magnesia carbon bricks, magnesium polycarboxylate, magnesium citrate, mesophase asphalt and catalyst weighed in step (1) and ball milling for 35 to 50 minutes to obtain a premix;

[0018] (3) adding a binder thermosetting phenolic resin to the premix obtained in step (2), and stirring in a mixer for 8 to 25 minutes to obtain a mixture;

[0019] (4) The mixture obtained in step (3) is pressurized and then sintered in a reducing atmosphere at 800-1200° C. to obtain a nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material.

[0020] The present invention also provides a method for preparing a preferred nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material, comprising the following steps:

[0021] (1) preparing raw materials according to the mass percentage of each raw material: 88% to 95% of fused magnesia sand, 0% to 3% of magnesia carbon brick, 0.5% to 4% of polycarboxylate magnesium, 0% to 0.5% of magnesium citrate, 0.3% to 3% of mesophase pitch, 0.05% to 0.6% of catalyst, and 0.1% to 2% of binder;

[0022] (2) premixing the fused magnesia sand and magnesia carbon brick with a particle size of less than 1 mm weighed in step (1), magnesium polycarboxylate, magnesium citrate, mesophase asphalt and catalyst, and ball milling for 35 to 50 minutes to obtain a premix;

[0023] (3) adding the fused magnesia sand and magnesia carbon brick particles with a particle size of not less than 1 mm and a thermosetting phenolic resin as a binder weighed in step (1) to the premix obtained in step (2), and stirring in a mixer for 8 to 25 minutes to obtain a mixture;

[0024] (4) The mixture obtained in step (3) is pressurized and then sintered in a reducing atmosphere at 800-1200° C. to obtain a nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material.

[0025] According to the above scheme, in step (4), the pressure of the pressurized molding is 120-190 MPa, the sintering time is 2-4 hours, and the reducing atmosphere is charcoal sintering.

[0026] The functions and mechanisms of the main raw materials and main processes in the present invention are as follows:

[0027] The low-carbon magnesium-carbon refractory product of the present invention comprises a magnesium polycarboxylate (taking magnesium polyacrylate as an example) which is first decomposed at a high temperature of 800 to 1200° C. under the catalytic action of a catalyst nickel or iron, and the magnesium polyacrylate is mainly divided into two stages. The first stage is deacidification, that is, the carboxyl group on the main chain of the magnesium polyacrylate is first lost under heating to generate MgO; the second stage is depolymerization of the main chain of the magnesium polyacrylate, that is, the main chain of the magnesium polyacrylate breaks the CC bond under heating, and as the temperature rises, the molecular chain movement gradually intensifies, and the deacidified polymer molecules are decomposed into CC bonds of different sizes. In a reducing atmosphere and at a high temperature, CC chains of different lengths are carbonized to generate nano-carbon fibers, and are evenly and firmly combined with other components in the product, thereby ensuring the uniformity of the nano-carbon fibers in the product and the high strength of the product. In addition, the polymer of the CC bond is combined with other components in the raw material by chemical bonds during the depolymerization and polycondensation carbonization process, thereby ensuring the stability and thermal shock resistance of the product, and the product is not easy to be peeled off, which is beneficial to resisting slag erosion. The amount of magnesium polycarboxylate is limited to 0.5% to 4%, because magnesium polyacrylate is actually a carbon-containing polymer salt. If the content is too high, the final carbon content of the product will be higher. If the content is too low, it will not be easy to generate sufficient stable chemical bonds with other raw materials to form nano-carbon fiber components.

[0028] Moreover, the mesophase asphalt generates a kind of disc-shaped nematic small liquid crystals with parallel arrangement of the mesophase at about 400°C. This kind of mesophase small liquid crystals have both liquid and solid properties, have a certain fluidity, can fill the pores in the low-carbon magnesium-carbon refractory product of the present invention, and ensure the compactness of the product. The mesophase asphalt belongs to a high molecular polymer. In the process of preparing the low-carbon magnesium-carbon refractory product, it can be depolymerized and carbonized into carbon fibers at high temperature, which can enhance the oxidation resistance of the refractory material. The amount of mesophase asphalt is limited to 0.3% to 3%, because the mesophase asphalt is a high molecular polymer of carbon. If the content of the mesophase asphalt exceeds 3%, the total carbon content of the product will increase; if the content of the mesophase asphalt is less than 0.3%, the small liquid crystals generated at high temperature in the intermediate type are not enough to fill the gaps in the bricks, and are not enough to generate carbon fibers with greater strength, and thus cannot effectively improve the product's slag erosion resistance and thermal shock resistance.

[0029] In the present invention, magnesium citrate and magnesium polycarboxylate are dispersants themselves, have good dispersibility in the raw materials, do not agglomerate, are evenly distributed, can also discharge the gas in the raw materials, prevent the appearance of large air pores, and are beneficial to the stability of the performance of refractory materials. Magnesium polycarboxylate is a high molecular carbon-containing polymer, and magnesium citrate is a small molecular carbon-containing compound. They will decompose to produce magnesium oxide at high temperatures, and respectively generate CC bonds with other components in the raw materials, which can improve the product's antioxidant and thermal shock stability. The dosage of magnesium citrate is 0-0.5%, and a small amount of magnesium citrate and other components in the raw materials generate small molecular carbon-containing compounds, which are beneficial to promote the generation of nano-carbon; if the content is too high, the carbon content of the product will also increase, and it is not easy to form long-chain carbon fibers.

[0030] In addition, thermosetting phenolic resin has good thermosetting properties at high temperatures, which ensures the strength of low-carbon magnesium-carbon refractory products at high temperatures. No catalyst or accelerator is required when curing thermosetting phenolic resin, only heating and pressurization are required. After curing, the density of thermosetting phenolic resin is smaller than that of polyester resin, and it has good mechanical strength, chemical corrosion resistance and moisture resistance, high thermal strength and low deformation tendency. Under heating conditions, thermosetting phenolic resin undergoes complex condensation reactions and cross-linking reactions to generate small molecules that are discharged under high temperature and high pressure. This macromolecular long-chain compound combines with other components in the raw materials to generate high-strength refractory materials under high temperature and high pressure conditions. The dosage of thermosetting phenolic resin is 0.1% to 2%. If it is less than 0.1%, the thermosetting phenolic resin will not play the role of a binder at all. If it is >2%, the overall carbon content of the product will increase, which is not conducive to the preparation of low-carbon magnesium-carbon refractory materials.

[0031] The particle size of fused magnesia does not exceed 6 mm, and the mass percentage of particles in the range of 0.088 to 1 mm is 22% to 30%, the mass percentage of particles in the range of 1 to 3 mm is 29% to 34%, and the mass percentage of particles in the range of 3 to 6 mm is 32% to 41%. This is because the content of coarse particles with a particle size of 3 to 6 mm is relatively high, which can reduce the molding resistance of the material, increase the bulk density and room-temperature compressive strength of the material, reduce the porosity, and improve the corrosion resistance of the material.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The carbon content of the nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material of the present invention is 3.8% to 9.0%, while the carbon content of the traditional magnesium-carbon refractory material is 12% to 20%. The carbon content of the low-carbon magnesium-carbon refractory material of the present invention is lower than that of the traditional magnesium-carbon refractory material. Through microstructural analysis, the nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material of the present invention is evenly distributed by the nano-carbon fibers generated in situ. Through performance testing and analysis, the low-carbon magnesium-carbon refractory material of the present invention is subjected to oxidation resistance tests at 1300℃×3h and 1600℃×3h in atmospheric atmosphere, and the area of ​​the oxidized part is <3% after cooling and cutting; the thermal shock stability of 1100℃ water cooling is >50 times; the crucible method is used to conduct an experiment on the final slag of the converter, and the area ratio of slag erosion is measured after cold cutting and cutting after charcoal burning at 1600℃×3h. c / S0<5%(Note: S c is the area of ​​the cut surface eroded by slag after the converter slag is eroded by the crucible method, and S0 is the original area of ​​the cut surface); the low-carbon magnesium-carbon refractory material of the present invention has excellent oxidation resistance, thermal shock stability and slag erosion resistance.

[0034] (2) In the preparation process of the present invention, nanocarbon is generated by the reaction of polymers at high temperature to form carbon fibers, which have stronger bonding and are more evenly distributed in the refractory material, and can achieve ideal oxidation resistance, thermal shock stability and slag corrosion resistance under low-carbon conditions. In contrast, traditional low-carbon magnesium-carbon refractory materials add nanocarbon to the raw materials, which is not easy to disperse and easily affects the performance of the refractory material. DETAILED DESCRIPTION

[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.

[0036] Example 1

[0037] A nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material, whose raw material composition is as follows by mass percentage: 91% of fused magnesia sand, 2.6% of magnesium-carbon brick, 3.5% of magnesium polyacrylate, 0.02% of magnesium citrate, 1.3% of mesophase pitch, 0.08% of catalyst nano-nickel powder and 1.5% of binder thermosetting phenolic resin.

[0038] Among them, the MgO content in the fused magnesia is about 98wt%; the particle size of the fused magnesia does not exceed 6mm, and the mass percentage of the particle size in the range of 0.088-1mm is 28%, the mass percentage of the particle size in the range of 1-3mm is 32%, and the mass percentage of the particle size in the range of 3-6mm is 40%.

[0039] Magnesia carbon bricks are prepared by sorting out the waste magnesia carbon bricks, treating them by hydration, crushing and removing the iron from the waste magnesia carbon bricks, soaking them in water, drying them, crushing them, removing the iron from them, and then screening them; the mass percentage of the particles in the range of 0.088 to 1 mm is 57%, and the mass percentage of the particles in the range of 1 to 3 mm is 43%; the treated magnesia carbon bricks contain about 87wt% MgO and about 11% carbon.

[0040] Nano nickel powder or nano iron powder is a powder with a particle size range of 10 to 40 nm; the nickel content of nano nickel (analytical grade purchased on the market) is greater than 99wt%; the mesophase asphalt is a coal-based mesophase asphalt with a relative molecular weight of 5100 and a softening point of 430°C, and is a laboratory-synthesized mesophase asphalt; the specific gravity of the thermosetting phenolic resin is 1.22, and the solid mass percentage is 78%; the molecular weight of magnesium polyacrylate is 15000.

[0041] The preparation method of the above-mentioned nano carbon fiber reinforced low carbon magnesium carbon refractory material comprises the following steps:

[0042] (1) According to the raw materials and their index requirements in this embodiment, prepare the materials according to their respective mass percentages;

[0043] (2) premixing the fused magnesia, magnesia carbon bricks, magnesium polyacrylate, magnesium citrate, mesophase asphalt and catalyst nano nickel powder weighed in step (1), and then ball milling them in a ball mill for 40 minutes to obtain a premix;

[0044] (3) adding the thermosetting phenolic resin to the premix obtained in step (2) in batches, stirring in a stirrer for 20 minutes to obtain a mixture;

[0045] (4) The mixed material obtained in step (3) is subjected to pressure molding at 170 MPa, and sintered at 1100° C. for 3 hours in a reducing atmosphere (carbon burial) to obtain a nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material.

[0046] After testing, the nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material prepared in this embodiment has a volume density of 3.12 g / cm according to the refractory industry testing standard. 3 , carbon content is 4.6%, compressive strength is 10.1MP, and refractoriness is 1770℃. And, through microscopic analysis, there are a lot of nano-carbon fiber structures in the magnesia carbon brick.

[0047] Through industry standard testing and analysis, the low-carbon magnesium-carbon refractory material of this embodiment was subjected to an anti-oxidation test at 1300°C × 3h and 1600°C × 3h in an atmospheric atmosphere, and the area of ​​the oxidized part was 2.6% after cooling and cutting; the thermal shock stability of 1100°C water cooling was >58 times; the crucible method was used to test the final slag of the converter, and the area of ​​slag erosion was measured after cold cutting and cutting after charcoal burning at 1600°C × 3h. c / S0 is 3.2% (Note: S c = is the area of ​​the cut surface eroded by slag after the converter slag is eroded by the crucible method, and S0 is the original area of ​​the cut surface). Therefore, the low-carbon magnesium-carbon refractory material of the present invention has excellent oxidation resistance, thermal shock stability and slag erosion resistance.

[0048] Used in a steel plant's refining furnace, its service life is 12% longer than that of traditional magnesium-carbon refractory materials.

[0049] Example 2

[0050] A nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material comprises the following raw materials by mass percentage: 93.5% fused magnesia, 2.3% magnesium polyacrylate, 0.02% magnesium citrate, 2.9% mesophase pitch, 0.06% catalyst nano-iron powder and 1.22% binder thermosetting phenolic resin.

[0051] Among them, the MgO content in the fused magnesia is about 99wt%; the particle size of the fused magnesia does not exceed 6mm, and the mass percentage of the particle size in the range of 0.088-1mm is 25%, the mass percentage of the particle size in the range of 1-3mm is 30%, and the mass percentage of the particle size in the range of 3-6mm is 45%.

[0052] Nano iron powder is a powder with a particle size range of 10 to 25 nm; the iron content of nano iron (analytical grade purchased on the market) is greater than 99wt%; the mesophase asphalt is a coal-based mesophase asphalt with a relative molecular weight of 5600 and a softening point of 460°C, and is a laboratory-synthesized mesophase asphalt; the specific gravity of the thermosetting phenolic resin is 1.25, and the solid mass percentage is 81%; the molecular weight of magnesium polyacrylate is 13000.

[0053] The preparation method is as follows:

[0054] The preparation method of the above-mentioned nano carbon fiber reinforced low carbon magnesium carbon refractory material comprises the following steps:

[0055] (1) According to the raw materials and their index requirements in this embodiment, prepare the materials according to their respective mass percentages;

[0056] (2) premixing the fused magnesia, magnesium polyacrylate, magnesium citrate, mesophase asphalt and catalyst nano iron powder weighed in step (1), and then ball milling them in a ball mill for 50 minutes to obtain a premix;

[0057] (3) adding the thermosetting phenolic resin to the premix obtained in step (2) in batches, stirring in a stirrer for 20 minutes to obtain a mixture;

[0058] (4) The mixed material obtained in step (3) is subjected to pressure molding at 150 MPa, and sintered at 1200° C. for 3 hours in a reducing atmosphere (carbon burial) to obtain a nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material.

[0059] After testing, the nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material prepared in this embodiment has a volume density of 3.15 g / cm according to the refractory industry testing standard. 3 , carbon content is 4.2%, compressive strength is 10.8MP, refractoriness is 1780℃; and, through microscopic analysis, there are a large number of nano-carbon fiber structures in the magnesia carbon brick.

[0060] Through industry standard testing and analysis, the low-carbon magnesium-carbon refractory material of this embodiment was subjected to an oxidation resistance test at 1300°C × 3h and 1600°C × 3h in an atmospheric atmosphere, and the area of ​​the oxidized part was 2.9% after cooling and cutting; the thermal shock stability of 1100°C water cooling was >60 times; the crucible method was used to test the final slag of the converter, and the area of ​​slag erosion was measured after cold cutting and cutting after charcoal burning at 1600°C × 3h. c / S0 is 3.0%. Therefore, the low-carbon magnesium-carbon refractory material of the present invention has excellent oxidation resistance, thermal shock resistance and slag erosion resistance.

[0061] Used in a steel plant's refining furnace, its service life is 14% longer than that of traditional magnesium-carbon refractory materials.

[0062] Comparative Example 1

[0063] A nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material, whose raw material composition is as follows by mass percentage: 85% of fused magnesia sand, 1.4% of treated waste magnesium-carbon bricks, 8.7% of nano-carbon black, 1.3% of graphite, 0.1% of catalyst nano-nickel powder, and 3.5% of binder thermosetting phenolic resin.

[0064] Among them, the MgO content in the fused magnesia is about 98wt%; the particle size of the fused magnesia does not exceed 6mm, and the mass percentage of the particle size in the range of 0.088-1mm is 26%, the mass percentage of the particle size in the range of 1-3mm is 33%, and the mass percentage of the particle size in the range of 3-6mm is 41%.

[0065] Magnesia carbon bricks are made by sorting out the waste magnesia carbon bricks, using hydration treatment, crushing the waste magnesia carbon bricks to remove iron, soaking them in water, drying them, crushing them, removing iron, and then screening them. The mass percentage of particles in the range of 0.088-1mm is 60%, and the mass percentage of particles in the range of 1-3mm is 40%; among them, the MgO in the treated magnesia carbon bricks is about 86.1wt%, and the carbon is about 11.2%.

[0066] Nano carbon black (purchased from the market) has a particle size of about 18 nm; graphite particle size is 0.5 mm; nano nickel powder is a powder of 20 to 35 nm; the nickel content of nano nickel (purchased from the market of analytical grade) is greater than 99 wt %. The specific gravity of the thermosetting phenolic resin used is 1.24, and the solid mass percentage is 79.5%.

[0067] The preparation method of the above-mentioned nano carbon fiber reinforced low carbon magnesium carbon refractory material comprises the following steps:

[0068] (1) According to the raw materials and their index requirements in this embodiment, prepare the materials according to their respective mass percentages;

[0069] (2) premixing the fused magnesia, magnesia carbon bricks, nano carbon black, graphite and catalyst nano nickel powder weighed in step (1), and then ball milling them in a ball mill for 45 minutes to obtain a premix;

[0070] (3) adding the thermosetting phenolic resin to the premix obtained in step (2) in batches, stirring in a stirrer for 25 minutes to obtain a mixture;

[0071] (4) The mixed material obtained in step (3) is subjected to pressure molding at 175 MPa, and sintered at 1150° C. for 2.5 hours in a reducing atmosphere (carbon burial) to obtain a magnesium-carbon refractory material.

[0072] After testing, the volume density of the carbon magnesium carbon refractory material is 2.98g / cm according to the refractory industry testing standard. 3 , the carbon content is 10.6%, the compressive strength is 8.7MP, and the refractoriness is 1760℃; and, through microscopic analysis, there is no nano-carbon fiber structure in the magnesia carbon brick.

[0073] Through industry standard testing and analysis, the low-carbon magnesium-carbon refractory material of this comparative example was subjected to oxidation resistance test at 1300℃×3h and 1600℃×3h in atmospheric atmosphere, and the area of ​​oxidation was 5.6% after cooling and cutting; the thermal shock stability of 1100℃ water cooling was >46 times; the crucible method was used to test the final slag of the converter, and the area of ​​slag erosion was measured after cold cutting and cutting after charcoal burning at 1600℃×3h. c / S0 is 6.2%.

[0074] When used in a steel mill refining furnace, the service life is increased by 3% compared with the traditional magnesium-carbon refractory material. Since nano carbon black and graphite are used as carbon sources in the comparative example, although the addition of nano carbon is conducive to forming a dense magnesium-carbon material, the nano carbon is not easy to disperse evenly, and the nano carbon does not form a compact carbon nano fiber structure with other components in the material, the obtained material has poor stability, and the thermal shock resistance and slag erosion resistance are lower than those of the present invention, and the total carbon content is higher than that of the present invention.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A nanocarbon fiber reinforced low-carbon magnesium-carbon refractory material, characterized in that: Its raw materials include fused magnesia, magnesia carbon bricks, magnesium polycarboxylate, magnesium citrate, mesophase asphalt, catalyst and binder, wherein the catalyst is nano nickel and / or nano iron, and the binder is thermosetting phenolic resin; the raw materials are as follows by mass percentage: fused magnesia 88%-95%, magnesia carbon bricks 0-3%, magnesium polycarboxylate 0.5%-4%, magnesium citrate 0.02%-0.5%, mesophase asphalt 0.3%-3%, catalyst 0.05%-0.6%, and binder 0.1%-2%; The MgO content in the fused magnesia is greater than 97wt%; the particle size of the fused magnesia does not exceed 6mm, and the mass percentage of the particle size in the range of 0.088-1mm is 22%-30%, the mass percentage of the particle size in the range of 1-3mm is 29%-34%, and the mass percentage of the particle size in the range of 3-6mm is 32%-45%, and the total of the three is 100%; The preparation method of the nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material comprises the following steps: (1) Prepare the raw materials according to the mass percentage of each raw material: fused magnesia 88%~95%, magnesia carbon brick 0~3%, polycarboxylic acid magnesium 0.5%~4%, magnesium citrate 0~0.5%, mesophase pitch 0.3%~3%, catalyst 0.05%~0.6%, binder 0.1%~2%; (2) premixing and ball-milling the fused magnesia sand, magnesia carbon brick, magnesium polycarboxylate, magnesium citrate, mesophase asphalt and catalyst weighed in step (1) to obtain a premix; (3) adding a binder thermosetting phenolic resin to the premix obtained in step (2), stirring evenly to obtain a mixture; (4) Pressurizing the mixture obtained in step (3) and then sintering it in a reducing atmosphere at 800-1200° C. to obtain a nanocarbon fiber reinforced low-carbon magnesium-carbon refractory material; The volume density of the low-carbon magnesium-carbon refractory material is 2.9-3.3 g / cm 3 , carbon content is 3.8%~9.0%, compressive strength is 9.2~13.0MPa, refractoriness>1760℃, thermal shock stability of 1100℃ water cooling>50 times, slag erosion resistance S c / S0 is less than 5%.

2. The nanocarbon fiber reinforced low-carbon magnesium-carbon refractory material according to claim 1, characterized in that: The magnesia carbon bricks are prepared by sorting out the waste magnesia carbon bricks, removing the oxidized part, crushing, ball milling and screening, wherein the mass percentage of the particles in the range of 0.088-1 mm is 50%-80%, and the mass percentage of the particles in the range of 1-3 mm is 20%-45%, and the total of the two is 100%; wherein the MgO in the treated magnesia carbon bricks is not less than 84.0wt%.

3. The nanocarbon fiber reinforced low-carbon magnesium-carbon refractory material according to claim 1, characterized in that: The magnesium polycarboxylate is one or both of magnesium polyacrylate and magnesium polymethacrylate, and the relative molecular weight thereof is greater than 10,000.

4. The nanocarbon fiber reinforced low-carbon magnesium-carbon refractory material according to claim 1, characterized in that: The nano nickel or nano iron is a powder with a particle size ranging from 10 to 40 nm; the nickel content of the nano nickel is greater than 98 wt %, and the iron content of the nano iron is greater than 98 wt %.

5. The nanocarbon fiber reinforced low-carbon magnesium-carbon refractory material according to claim 1, characterized in that: The mesophase asphalt is coal-based mesophase asphalt, with a relative molecular weight of 1000-6000 and a softening point of 400-500° C.; the specific gravity of the thermosetting phenolic resin is 1.20-1.25, and the solid mass percentage is 70%-85%.

6. The method for preparing the nanocarbon fiber reinforced low-carbon magnesium-carbon refractory material according to any one of claims 1 to 5, characterized in that: The steps include: (1) Prepare the raw materials according to the mass percentage of each raw material: fused magnesia 88%~95%, magnesia carbon brick 0~3%, polycarboxylic acid magnesium 0.5%~4%, magnesium citrate 0.02%~0.5%, mesophase pitch 0.3%~3%, catalyst 0.05%~0.6%, binder 0.1%~2%; (2) premixing and ball-milling the fused magnesia sand, magnesia carbon brick, magnesium polycarboxylate, magnesium citrate, mesophase asphalt and catalyst weighed in step (1) to obtain a premix; (3) adding a binder thermosetting phenolic resin to the premix obtained in step (2), stirring evenly to obtain a mixture; (4) The mixture obtained in step (3) is pressurized and then sintered in a reducing atmosphere at 800-1200° C. to obtain a nanocarbon fiber reinforced low-carbon magnesium-carbon refractory material.

7. According to the method for preparing a nano-carbon fiber reinforced low-carbon magnesium-carbon refractory material according to claim 6, in step (4), the pressure of the pressurized molding is 120-190 MPa, the sintering time is 2-4 hours, and the reducing atmosphere is charcoal sintering.

Citation Information

Patent Citations

  • Nanocarbon reinforced low-carbon magnesia carbon brick and preparation method thereof

    CN108484130A

  • Low-carbon magnesia carbon brick with oxidation resistance and preparation method thereof

    CN113461407A

  • Antioxidant low-carbon magnesia carbon brick and preparation method thereof

    CN114180941A

  • Low-carbon magnesia carbon brick with bar or lamellar reinforcing structure and preparation method thereof

    CN101823890A

  • Combined-phase reinforced low-carbon MgO-C refractory material and preparation method thereof

    CN109867529A